2020
DOI: 10.1016/j.jjcc.2019.07.011
|View full text |Cite
|
Sign up to set email alerts
|

Effects of carvedilol vs bisoprolol on inflammation and oxidative stress in patients with chronic heart failure

Abstract: The effects of beta-blockers on long-term morbidity and mortality have been established in patients with chronic heart failure (CHF) with reduced left ventricular function [1][2][3][4]. Among various beta-blockers, only carvedilol and bisoprolol are approved by Japanese guidelines for the treatment of patients with CHF [5]. Bisoprolol is highly selective for the beta-1 receptor, whereas carvedilol is a non-selective beta-blocker with simultaneous alpha-receptor antagonism [6]. However, there is no established … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 40 publications
1
17
0
2
Order By: Relevance
“…The authors concluded that both compounds have beneficial effects. They concluded that carvedilol was more effective in reducing oxidative stress, an effect repeatedly shown for carvedilol treatment (Toyoda et al, 2020).…”
Section: Discussionmentioning
confidence: 77%
“…The authors concluded that both compounds have beneficial effects. They concluded that carvedilol was more effective in reducing oxidative stress, an effect repeatedly shown for carvedilol treatment (Toyoda et al, 2020).…”
Section: Discussionmentioning
confidence: 77%
“…Mitochondrial dysfunctions play an important role in CVDs pathogenesis [ 355 ]; however, there are no medications to modulate mitochondrial functions available in clinical practice [ 406 ]. However, therapeutic agents have been investigated to target mitochondrial, including the mitochondria-targeted antioxidant MitoQ1, that decreases ROS production and has shown protective effect in hypertensive rat models [ 407 ], and carvedilol or antidiabetic drugs that prevent cardiac mitochondrial oxidative damage [ 408 ]. Therapies targeting endothelial NO synthase (eNOS) activity and function, using statins, ACE inhibitors, and AT1-receptor blockers, have been shown to improve cardiovascular prognosis by decreasing the level of oxidative stress, inflammation, and mediators of vascular dysfunctions [ 409 , 410 ].…”
Section: Cardiovascular Diseases (Cvds)mentioning
confidence: 99%
“…Carvedilol shifts the heart energy substrate usage from fatty acids to glucose oxidation [ 315 , 368 ] by decreasing free fatty acids, inhibiting fatty acid oxidation, resulting in increased glycolysis, oxidation and energy efficiency [ 364 , 395 , 414 , 415 ] ( Figure 2 ). Mechanisms of cardioprotective effects of carvedilol are linked to oxidative metabolism and decreases in oxidative stress [ 102 , 327 , 363 , 414 , 415 , 416 , 417 , 418 ], which reduces the impairment of mitochondrial metabolism during HF [ 419 ]. Carvedilol can also improve insulin sensitivity and plasma lipid profile [ 419 , 420 , 421 ].…”
Section: Ars In Cardiac Metabolism and As Potential Therapeuticsmentioning
confidence: 99%
“…Mechanisms of cardioprotective effects of carvedilol are linked to oxidative metabolism and decreases in oxidative stress [ 102 , 327 , 363 , 414 , 415 , 416 , 417 , 418 ], which reduces the impairment of mitochondrial metabolism during HF [ 419 ]. Carvedilol can also improve insulin sensitivity and plasma lipid profile [ 419 , 420 , 421 ]. The net effect of these metabolic changes are favorable effects on glucose metabolism [ 412 , 421 ], by improving myocardial energy efficiency through increased carbohydrate utilization [ 395 , 422 , 423 ], similar to α 1A -AR agonism.…”
Section: Ars In Cardiac Metabolism and As Potential Therapeuticsmentioning
confidence: 99%